PENINGKATAN MUTU SDM DESA BELITAR SEBERANG MELALUI PENERAPAN E-TOURISM MENUJU OBYEK WISATA INTERNASIONAL - Fadlul Amdhi Yul Amdhi; Mesterjon; Jumiati Siska; Yenni Fitria; Tiara Lestari; Yocia Deana Putri (Abdi Reksa, 2023)
To realize the development of Belitar Village towards international tourism objects, active participation of the community is needed in developing the tourism sector by utilizing technology. Smart tourism-based tourism is a new ecosystem that can support and facilitate the creation of new innovations related to the use of technology and the development of smart tourism experiences. The purpose of this community service activity is to improve community skills in promoting, managing tourism and enlarging a wider industrial scale. PKM activities are carried out by providing training to tourism managers in implementing E-Tourism. The results of PKM are known to increase skills and knowledge in using Information Technology such as the use of social media, E-Commerce to support tourism management activities.